2013
DOI: 10.1021/ja404428u
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of In-Membrane Receptor Clustering upon Binding of Multivalent Ligands

Abstract: In living cells and biomimetic systems alike, multivalent ligands in solution can induce clustering of membrane receptors. The link between the receptor clustering and the ligand binding remains, however, poorly defined. Using minimalist divalent ligands, we develop a model that allows quantifying the modulation of receptor clustering by binding of ligands with any number of binding sites. The ligands, with weak binding affinity for the receptor and with binding sites held together by flexible linkers, lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…The data suggest that preclustering of the receptor ligands (in this case, biotin anti-CD95) on oil drops is directly correlated to the effectiveness of inducing apoptosis through the CD95 receptor. This result is consistent with the known effect of the CD95 receptor clustering on apoptosis (30)(31)(32)(33).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The data suggest that preclustering of the receptor ligands (in this case, biotin anti-CD95) on oil drops is directly correlated to the effectiveness of inducing apoptosis through the CD95 receptor. This result is consistent with the known effect of the CD95 receptor clustering on apoptosis (30)(31)(32)(33).…”
Section: Resultssupporting
confidence: 91%
“…Conjugation of antibodies and ectodomains on nanoparticles (34) and liposomes through chemical reactions (35) or affinity tags (27) intends to mimic the cell surface, but the orientation and position of chemically conjugated protein ligands can be difficult to control. It is not possible to form extensive clusters on nanoparticles and liposomes that can potentially induce strong biological responses (32,33). In contrast, ssMPs are more likely to orient properly on oil drops, capable of being spatially clustered, and in a fluidic environment that facilitates the communication with receptors on cell surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…In living cells, phenomena such as signal transduction, which are fundamental for immunological responses and neurotransmission, are oen associated with the formation of domains and the clustering of receptors at a cell surface. [1][2][3] Multivalent ligand-receptor interactions at the interface, in combination with the uidity of the cell membrane, promote the rearrangement and co-localization of receptors on a surface, and thereby govern these biological responses. 4 The molecular processes of binding, diffusion and clustering occur at characteristic length and time scales, and these can be distinctly different from those associated with the biological processes that they induce.…”
Section: Introductionmentioning
confidence: 99%
“…If clustering is taken as the rate-limiting step in cellular uptake kinetics, then it follows, logically, that the greater the residence time on the membrane the higher the probability to form NP clusters and consequently the greater the uptake. 43,44 Indeed, more GNRs were found adjacent to the membrane for the longest nanorod than any of the shorter ones. These observations are in close agreement with the predictions of Gao et al who showed that the increased uptake of larger NPs, or clusters, is due to the high membrane bending energies associated with the endocytosis of smaller NPs.…”
Section: Comparison With Modelsmentioning
confidence: 99%